Seven ways to change the world : reviving faith and politics - Wallis, Jim. (Oxford : Lion, 2008)
In Seven Ways to Change the World, Jim Wallis argues that politics has failed to solve the biggest issues of our time: extreme and needless poverty, global warming and environmental degradation, terrorism and the endless cycle of violence, racism, human trafficking, health and education, respect for human life and the crisis in families and parenting. Whatever happened to the 'common good'? Writing out of a US context but applicable to the wider world, Wallis helps us rediscover our moral centre and infuses us with the inspiration and passion we need to chart a new course and build the kind of movements that change politics.
Includes bibliographical references and index.
Keywords: Christianity and politics; Religion and politics; Religion -- Social aspects